The Role of Shopping Engagement and Customer Experience on Intention to Buy based on Technology Acceptance Model in Gen Z - Dwipradhana, Nanda Ayoe Rizky; Marsasi, Endy Gunanto (JDM (Jurnal Dinamika Manajemen), 2024)
The research aims to find out the relationship between shopping gamification, focused attention, shopping enjoyment, and intention to buy mediated by shopping engagement in Generation Z in online food delivery apps. Indonesian consumer’s shopping habits on the internet have grown rapidly recently. The majority of Indonesian consumers prefer to use mobile apps on their smartphones. Customer experience added as a novelty to the research and Technology Acceptance Model is used as the main theory in this study. The method in this study uses a quantitative approach using purposive sampling technique that produces 195 samples. This study found that customer experience did not influence shopping engagement. Purchasing intentions are positively influenced by shopping engagement. This study is useful for online food delivery app managers so it can provide exclusive offers to users to increase shopping engagement. This research shows that a good customer experience may be able to increase customer engagement while shopping, however it does not necessarily have a positive impact on customer loyalty levels.